Efektivitas Pelapisan Benih (Seed Coating) Berbahan Aktif Cendawan Antagonis Untuk Mengendalikan Penyakit Rebah Kecambah (Damping Off) Kacang Tanah - Sukma Karina Putri; Abdul Majid (Fakultas Pertanian Universitas Jember, 2019)
Peanut (Arachis hypogaea L.) is one of the strategic commodities in agriculture that is widely used as food and oil preparations. The constraint in the production of peanut is the Slclerotium rolfsii Sacc attack which causes a loss of 40-75%. Alternative control that using the antagonist Trichoderma harzianum with coating techniques. The purpose of this study was to determine the effect of the addition of T. harzianum with coating techniques in suppressing S. rolfsii and their effect on seed viability. This research was carried out at the Plant Protection Laboratory and at Green House of the Faculty of Agriculture, University of Jember With the research design used a Factorial Complete Randomized Design. Consisting of 2 factors. The result showed that P2W1 (Kaolin and 1-week storage) effectively controlled S. rolfsii with an effectiveness value of 61,7% extending the 12 days after inoculations for incubation period, being able to maintain a better population of biological agents, 30 % severity, 100 % of viability, dry weight 11,74 grams, and 49,98 % or incidence.